Neuromedin-U Mediates Rapid Activation of Airway Group 2 Innate Lymphoid Cells in Mild Asthma - Ju, Xiaotian; Nagashima, Akimichi; Dvorkin-Gheva, Anna; Wattie, Jennifer; Howie, Karen; Whetstone, Christiane; Ranjbar, Maral; Cusack, Ruth; Ditta, Reina; Paré, Guillaume; Satia, Imran; O’Byrne, Paul M.; et al. (American journal of respiratory and critical care medicine, 2024)
In asthma, sputum group 2 innate lymphoid cells (ILC2s) are activated within 7 hours after allergen challenge. Neuroimmune interactions mediate rapid host responses at mucosal interfaces. In murine models of asthma, lung ILC2s colocalize to sensory neuronal termini expressing the neuropeptide neuromedin U (NMU), which stimulates type 2 (T2) cytokine secretion by ILC2s, with additive effects to alarmins . To investigate the effect of the NMU/NMUR1 (NMU receptor 1) axis on early activation of ILC2s in asthma. Subjects with mild asthma ( = 8) were enrolled in a diluent-controlled allergen inhalation challenge study. Sputum ILC2 expression of NMUR1 and T2 cytokines was enumerated by flow cytometry, and airway NMU levels were assessed by ELISA. This was compared with samples from subjects with moderate to severe asthma ( = 9). Flow sort-purified and -expanded ILC2s were used for functional assays and transcriptomic analyses. Significant increases in sputum ILC2s expressing NMUR1 were detected 7 hours after allergen versus diluent challenge whereby the majority of NMUR1 ILC2s expressed IL-5/IL-13. Sputum NMUR1 ILC2 counts were significantly greater in mild versus moderate to severe asthma, and NMUR1 ILC2s correlated inversely with the dose of inhaled corticosteroid in the latter group. Coculturing with alarmins upregulated in ILC2s, which was attenuated by dexamethasone. NMU-stimulated T2 cytokine expression by ILC2s, maximal at 6 hours, was abrogated by dexamethasone or specific signaling inhibitors for mitogen-activated protein kinase 1/2 and phosphoinositol 3-kinase but not the IL-33 signaling moiety MyD88 . The NMU/NMUR1 axis stimulates rapid effects on ILC2s and may be an important early activator of these cells in eosinophilic inflammatory responses in asthma.